1999
DOI: 10.1200/jco.1999.17.2.631
|View full text |Cite
|
Sign up to set email alerts
|

Preradiotherapy Computed Tomography as a Predictor of Local Control in Supraglottic Carcinoma

Abstract: Pretreatment CT measurements of tumor volume permits stratification of patients with supraglottic SCC treated with RT alone (which allows preservation of laryngeal function) into groups in which local control is more likely and less likely. Pre-epiglottic space spread is not a contraindication to using RT as the primary treatment for supraglottic SCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
116
0
8

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 20 publications
5
116
0
8
Order By: Relevance
“…Plataniotis et al [29] found that GTV correlated with treatment outcomes for patients with locally advanced HNSCC treated with radiation therapy or radiation therapy plus chemo therapy. Several authors also reported that GTV obtained from CT scan was a significant predictor for clinical outcome in the treatment of HNSCC [10,[30][31][32]. A few articles suggested that the larger MR-derived GTV was associated with higher recurrence and poorer survival rates [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Plataniotis et al [29] found that GTV correlated with treatment outcomes for patients with locally advanced HNSCC treated with radiation therapy or radiation therapy plus chemo therapy. Several authors also reported that GTV obtained from CT scan was a significant predictor for clinical outcome in the treatment of HNSCC [10,[30][31][32]. A few articles suggested that the larger MR-derived GTV was associated with higher recurrence and poorer survival rates [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…GTV appears to be the strongest independent predictor of local failure after RT. 9 Pretreatment CT measurements of GTV permit stratification of local control in patients with SGSCCA who receive treatment with RT alone. Mancuso et al reported local control rates of 89% in tumors Ͻ 6 cc and 52% when tumor volumes were Ն 6 cc.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17] Threshold volumes have been identified in nasopharyngeal, oropharyngeal, supraglottic, pyriform sinus, and T3 glottic carcinomas. [5][6][7][8][9][10][11][12][13][14][15][16][17] Several investigators also have shown that there is a stronger association between GTV and local control than the association between T classification and local control. 6,7,[15][16][17][18] This additional information helps physicians to counsel patients regarding the relative likelihood of local tumor control with primary surgery or RT with or without chemotherapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations